The Influence of Foreign Tourists Existence on Language Behaviour of Creative Economics : A Case Study of Floating Market, South Kalimantan, Indonesia - Rahma Pitria Ningsih; Susilawati Susilawati (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2022)
Floating market is not only a place where many products from rural areas can be traded, but it also provides a one-of-a-kind view of life on the water in the form of many small boats. This community's well-known adherence to a particular exotic tradition has proven quite successful in drawing tourists not only from within but also from outside the country. The majority of people in the floating market speak English, despite the fact that many of the locals continue to communicate with one another in Banjar, which has, of course, some degree of impact on the creative economy actors there. The purpose of this study is to investigate whether or not there is an impact of travelers from other countries on the language patterns of creative economic actors. In this study, we make use of qualitative research methods. The descriptive method is used to carry out analysis. According to the findings of the research, it is common knowledge that fluency in multiple languages is an essential component of the persona of economically creative actors. This research was successful in revealing, among other things, that the manner of language demonstrated was capable of recognizing the behavior and personality of the speaker.